Code Switching and Code Mixing Used by Dian Sastrowardoyo in Daniel Mananta Network Youtube Channel - Yanuardi, Dimas (EDUJ : English Education Journal, 2023)
The purpose of this research is to discover and gain a deeper understanding, for both writer and readers, regarding the use of code switching and code mixing when someone speaks, specifically during a podcast. For this research, the writer uses qualitative method in analyzing the data contained within the research information, namely Code Switching and Code Mixing used by an actress named Dian Sastrowardoyo in a video titled Cerita Hidup Seorang Dian Sastrowardoyo - Daniel Tetangga Kamu Youtube video in Daniel Mananta Network Youtube channel. The results of the study show that there are 321 utterances spoken by Dian in the video. The most dominant type for Code Switching is intra-sentential code switching, and Code Mixing is intra-sentential code mixing. The most dominant reason of Dian's code switching and mixing is talking about a particular topic.